The role of modality and awareness in language learning. (3rd May 2021) - Zhao, Chuqi; Kormos, Judit; Rebuschat, Patrick; Suzuki, Shungo
Abstract: There is conflicting empirical evidence regarding the role of awareness in second language learning. Possible explanations for the contradictory results include the modality in the exposure and assessment phases of previous experiments. Our study investigated the acquisition of a novel determiner system under incidental exposure conditions and examined the effect of modality in both exposure and assessment phases. Animacy served as a hidden regularity in the determiners, which were embedded in sentences and presented to Chinese speakers of English either in auditory or in visual mode. Learning was assessed by a two-alternative forced-choice test either auditorily or in writing. Implicit and explicit knowledge were measured using retrospective verbal reports and source judgements. Bayesian analysis provided moderate evidence for above chance level learning. Significant learning effects were observed regardless of whether participants based their accuracy judgements on explicit or implicit knowledge. Bayesian analysis showed moderate evidence for above chance learning effects for aware participants. Generalized linear mixed-effects modeling revealed a small-size significant benefit of the auditory exposure modality over the written modality but indicated no significant effect of the modality of assessment or awareness. Our research underscores the importance of considering the role of modality of exposure in incidental second language learning contexts.